A Comparative Study of the Characteristics and Dynamics of the Smile in Patients with Skeletal Class II div I malocclusion in comparison with the Class I malocclusion (Journal of Hama University, 2021)
This study aimed to evaluate the smile  between patients with skeletal Class II div1 malocclusion in comparison  with those of normal occlusion  .Fourty patients who were listed in the records of the Department of Orthodontics – Faculty of Dentistry -University of Hama were chosen and then divided equally into two groups : the Class II div 1 group , and the Class I group ,Short videos were filmed for all patients in both groups and two photographs were taken in the frontal view ;the first photograph was taken at the rest position and the other represented the unrestricted social smile position .The data was analyzed by using unidirectional variance analysis (ANOVA).The changes in the height of the commissure, the gingival width, the length of the upper incisors, and the interlabial gap were higher in patients of skeletal  Class II div 1 .The arc of the smile was inverted  in the patients of the skeletal Class II div1, and the height of the smile arc was more noticeable in skeletal Class II div 1 compared to the Class I.The results of this study showed that the skeletal ClassII div1 malocclusion causes changes in the characteristics of the  smile and changes  in the position of the upper lip in the rest positions.